Penetapan Harga Jual Dengan Metode Variable Costing: Studi Kasus Pada Bengkel Kanopi Mandiri Welder - Dewi Maya Sari; Irli Attahira; Muhammad Abthahi (Jurnal Penelitian Ekonomi Akuntansi, 2025)
This research aims to analyze the pricing of products at Bengkel Kanopi Mandiri Welder using the variable costing method. The purpose of this study is to use the variable costing approach to examine Bengkel Kanopi Mandiri Welder's product pricing. This approach places a strong emphasis on allocating variable expenses that are closely associated with the manufacturing process. Direct observation and documenting of the production processes for both large and small minimalist grilles were used to gather data. The analysis's findings indicate that the company's selling price and the production cost determined using the variable costing method diverge. The selling price of the company's products is typically higher than the production cost determined by that approach. This discrepancy suggests that the business could generate a sizable profit margin, but it must also be assessed to guarantee effectiveness and market-competitive pricing. This study has limitations in that its scope is still limited to one type of business and product, and it does not consider external factors such as fluctuations in raw material prices and market conditions. For further research, it is recommended to conduct analyses on various types of products over a longer time period and use comparative methods such as full costing or activity-based costing to provide more comprehensive research results.